Motivation of personnel for career growth - Litynska, Valentyna; Popeliushko, Roman; Romanovska, Liudmila; Kravchyna, Tetiana; Snitsar, Inna (Edelweiss Applied Science and Technology, 2024)
The purpose of the study is to develop scientific approaches to determining motivation methods that affect the career growth of employees depending on their length of service in the organization. The article identifies the main reasons for the insufficient use of personnel motivation methods aimed at fostering their career growth. In addition, three main stages in the career growth of personnel are defined: the stage of professional adaptation, the internal stage and the stagnation stage. Accordingly, at each stage there is a need to use certain motivational methods. The article also analyzes the components of motivation for career growth of employees with different years of experience in the organization. The research is based on the methods of survey, questionnaire, observation, self-observation and the correlation method according to the Spearman criterion. The study of motivation for career growth of employees was carried out according to the following structural components: career intuition, career involvement, career stability, orientation to power, material reward (orientation to money), aspiration to status growth, aspiration to achievement. It has been found out that the average indicators of the components of career motivation also change among employees depending on their length of service. Thus, the most significant correlations between the components of motivation for career growth were determined, in particular between the need for achievements and career involvement; career intuition and career involvement; career stability and the desire for status growth; career stability and orientation to power; orientation to power and orientation to money.